Persepsi Tentang Tugas dan Motivasi Kerja Serta Pengaruhnya terhadap Kinerja Guru BK SMPN se-Kota Kupang - Wens Nagul; A Muri Yusuf; Syahniar Syahniar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2013)
This study is setting of issues about how the perception of task and work motivation influencing much on the performance of BK teacher/counselor at Junior High Schools in Kupang city. The goal is to describe the influence of perception on task and work motivation of BK teacher/counselor in the performance of duties in the school. The research uses a quantitative approach with descriptive methods. The results of this study showed that the perception of task and work motivation of BK teacher/counselor give a very significant influence on the performance of BK teachers/counselor in execution of duty.